Developing english reading comprehension skills in computer science and information technology students - Goncharenko, T. Y.; Vnukova, K. V.; Koliada, I. V. (Видавництво Житомирського державного університету імені Івана Франка, 2025)
The article examines contemporary methods of teaching reading for specific purposes to students of Computer Science and Information Technology, focusing on the development of discipline-oriented reading comprehension skills essential for academic and professional communication. Particular attention is given to integrating effective reading strategies within the framework of English for Specific Purposes (ESP), including skimming, scanning, intensive and critical reading, as well as strategy training aimed at improving learners’ autonomy. These strategies are presented as essential tools for understanding, analysing, and interpreting professional English texts that reflect the rapidly evolving discourse of the modern IT industry and require familiarity with complex terminology, conceptual structures, and genre-specific conventions. The study highlights the methodological value of task-based learning, the use of authentic materials, and the incorporation of multimodal resources such as technical documentation, tutorials, and online platforms. A significant emphasis is placed on expanding students’ vocabulary through systematic work with domain-specific terminology, lexical patterns, and collocations typical of Computer Science and IT, which strengthens learners’ ability to recognise linguistic cues and interpret specialised discourse more accurately. The article offers a structured review of professional texts, documentation, and online resources, accompanied by targeted reading and comprehension tasks implemented during practical classes with second- and third-year students. The results of classroom application demonstrate that taskbased activities, authentic materials, and guided strategy instruction contribute to the formation of higher-order reading skills, enhance students’ ability to process complex professional information, and improve their readiness to work with English-language sources in academic and industry-related settings. The study concludes that the proposed approach effectively supports the development of confidence, independence, and professional literacy in the field of Computer Science and Information Technology.

У статті досліджено сучасні методи навчання читання для спеціальних цілей студентів спеціальностей "Комп’ютерні науки" та "Інформаційні технології", зосереджуючи увагу на формуванні фахових умінь розуміння англомовних текстів, необхідних для академічної та професійної комунікації. Окремо розглядається інтеграція ефективних стратегій читання в межах підходу English for Specific Purposes (ESP), зокрема смислового перегляду, вибіркового читання, інтенсивного та критичного читання, а також навчання стратегіям, що сприяє підвищенню автономії здобувачів освіти. Зазначені стратегії подано як ключові інструменти для опрацювання професійних англомовних матеріалів, які відображають динамічний дискурс сучасної ІТ-індустрії та вимагають володіння складною термінологією, концептуальними структурами й жанровими особливостями. У дослідженні підкреслено методичну цінність використання навчання на основі виконання завдань, застосування автентичних матеріалів і залучення мультимодальних ресурсів, зокрема технічної документації, навчальних платформ та онлайн-джерел. Значну увагу приділено розширенню словникового запасу через систематичну роботу з термінами галузі комп’ютерних наук, характерними лексичними моделями та колокаціями, що підсилює здатність студентів точніше інтерпретувати спеціалізований дискурс. У статті подано структурований огляд професійних текстів, документації та інтернет-джерел разом із комплексом цільових завдань з читання та розуміння, реалізованих під час занять зі студентами другого і третього курсів. Результати практичного впровадження засвідчують, що завдання, основані на реальних матеріалах, а також цілеспрямоване навчання стратегіям читання сприяють формуванню навичок вищого рівня, підвищують здатність опрацьовувати складну професійну інформацію та покращують готовність працювати з англомовними джерелами у галузі комп’ютерних наук й інформаційних технологій. Зроблено висновок, що запропонований підхід ефективно підтримує розвиток упевненості, самостійності та професійної грамотності студентів.
Формування навичок читання та розуміння англійських текстів у студентів комп’ютерних наук та інформаційних технологій
Keywords: reading strategies; English for specific purposes (ESP); reading comprehension; computer science; information technology; academic literacy; professional texts; domain-specific terminology; стратегії читання; англійська мова для спеціальних цілей (ESP); розуміння прочитаного; комп'ютерні науки; інформаційні технології; академічна грамотність; тексти професійної спрямованості; предметно-спеціальна термінологія